The Adolescent Athlete A Practical Approach (Contemporary Pediatric and Adolescent Sports Medicine,, 2018)
Now in a revised and updated second edition, this practical text on the adolescent athlete provides penetrating insights into musculoskeletal care for growing athletes. Chapters are logically organized by anatomical region and are written by experts in the field, focusing on improved clinical decision-making and addressing both chronic and acute injuries in addition to congenital conditions. Fundamentals, including basic anatomy, physical examination, and patient history, are covered in detail, with emphasis on the recognition of injury patterns unique to adolescent athletes. User-friendly tables are incorporated to assist with diagnosis. Prevention, patient management, and clinical pearls are each outlined, and return-to-play guidelines are highlighted. To further facilitate comprehensive patient care, musculoskeletal diagnostic imaging and principles of rehabilitation are covered as well. Anatomical drawings, photos of examination maneuvers, and diagnostic images, such as x-rays and MRI scans, complete the text by illustrating key concepts. Intended for sports medicine physicians, primary care physicians, orthopedists, physiotherapists and athletic trainers, this second edition of The Adolescent Athlete: A Practical Approach continues to be a sought-after resource for all who aim to improve the musculoskeletal health of active children and adolescents.